Emphasis of internal control and its scope in tax deductions (National Administration Journal, 2020)
Internal control represents the backbone of any economic entity anywhere in the world. Not only does it support but it also maintains the right balance between goals and outcomes. Through this research, internal control and its components are analyzed to show its influence in the field of tax deductions. A quantitative approach is used with a fully explanatory design to clearly and adequately convey the data and information obtained from fifty taxpayers in the state of Tabasco, Mexico.  The results lead to show that internal control is a business catalyst that affects the legal area, particularly in fiscal matters. It is the financial entities that, in order to assume business continuity, undertake this process to reach the objectives in an unlimited time horizon.
Keywords: Internal control; tax deductions; economic entity